Correlation between objective evaluation and subjective evaluation of facial profile in skeletal type ii females - Miss Choki (2022)
Objectives: The objective of this study was to find the cephalometric measurements that correlate with the visual perception. Materials and Methods: A total of 250 lateral cephalograms of patients from the year 2016 to 2018 were hand traced and analyzed. Thirty-six hard-and soft-tissue measurements were obtained from the lateral cephalometric analysis. Silhouettes obtained from cephalometric films were rated by 10 orthodontists based on their level of convexity. For each sample, the rating of visual perception was correlated with all the cephalometric (hard and soft) measurements. Results: ANB, AF-BF, L1-NB (mm), overjet, anterior maxillary alveolar height, posterior maxillary alveolar height, lower lip to E plane, and H angle were positively correlated with the visual perception. On the contrary, Pg. to N perpendicular and Pg. to NB (mm) were negatively correlated with the visual perception. However, the measurements in the vertical dimensions did not have any significant correlations with visual perception. H angle showed a higher correlation with visual perception than the nasolabial angle, facial contour angle, and lower lip to E plane. Conclusion: The agreement between objective cephalometric measurements and subjective visual perception was less than expected. In general, only 27% of the cephalometric measurements had a significant correlation with visual perception. Therefore, orthodontic treatment planning based solely on cephalometric analysis can result in unsatisfactory treatment outcomes. An inclusion of subjective measures such as visual perception in orthodontic diagnosis and treatment planning is necessary.